Spatial-Temporal Variation of Land Use Changes In Ambon City - Mohammad Amin Lasaiba (Rekayasa, 2023)
Changes in land use have caused various spatial consequences that occur substantially in an area. This study examines the pattern of land use changes from different room variations. The research was at a location in Ambon City. The materials in this study are Landsat 8 OLI/TIRS in 2010 and 2020, DEM SRTM, administrative maps, and development center maps. Research data were analyzed descriptively analytical, spatial, and temporal from the overlay results. The study results in show changes over ten years (2010-2020), indicating an increase in settlements covering an area of 23,810 ha per year. Differences in spatial variations based on administrative site, additional blocks in Sirimau District covering an area of 76,880 ha, and withdrawal of the most significant land in mixed gardens surrounding an area of 58,859 ha. In addition, there was additional weaponry on steep slopes (15 -30%) covering an area of 38,503 ha and a protected area of 16,505 ha by converting the use of forest land covering an area of 17,366 ha, and most of it took place in the city center. The addition of settlements also occurred in an accessibility (less than 3 km) area of 116,370 ha, most scattered in the secondary center of 86,520 ha.